Pengaruh Metode Pembelajaran dan Sikap Siswa pada Mata Pelajaran Sejarah Terhadap Hasil Belajar Sejarah Siswa di SMA Pondok Karya Pembangunan Jakarta Timur - Andi Andi (Jurnal Pendidikan Sejarah, 2017)
The aim of this research is to find out the effect of learnning method and students attitude on history studies to the result of student’s history learning in SMA Pondok Karya Pembangunan Jakarta Timur. This reseacrh is quantitative research that used experiment design treatment method by level 2x2. Instrument that writer used to measure the student’s attitude is questioner, and instrument that writer used to measure the result of learning is Multiple Choice. The result of research showed those (1). The result of learning history that students used mind mapping were higher than students in convensional learning. (2) there is interaction’s effect between the method of learning and student’s attitude. (3) the result of student’s history learning that use mind mapping have positive attitude is higher than student which use convensional learning. (4) the result of learning history, the students were used mind mapping method have negative’s attitude lower than students used convensional learning which have negative attitude